A Comprehensive Review: Plantar Fasciitis in Geriatric Patients in Indonesia: Ulasan Komprehensif: Fasciitis Plantaris pada Pasien Geriatri di Indonesia - Henry Ricardo Handoyo; Paul L Tahalele; Andre Young; Kevin Samsudin; Yovita Vivi Megasari; Gumelar, Agustinus Bimo; Ageng Salmanarrizqie (Universitas Andalas, 2025)
Plantar fasciitis is a degenerative condition affecting the connective tissue in the heel, characterized by pain at the medial plantar tuberosity of the calcaneus. It commonly occurs in elderly individuals aged 60 and above, with most cases resolving without treatment. However, therapeutic options become limited for older patients, particularly those aged 40 and above. This study evaluates various treatment methods for geriatric patients with plantar fasciitis, focusing on both medical and non-medical approaches. A comprehensive review of 19 relevant journals from 2000 to 2024 was conducted, analyzing treatments and their effectiveness in elderly populations. The results consistently demonstrated that Platelet-Rich Plasma (PRP) injections were highly effective in treating plantar fasciitis in elderly patients. No non-injection treatments were found to surpass the efficacy of PRP. Further research is needed to explore additional effective therapies for geriatric plantar fasciitis beyond PRP.